Apparent molar properties of glycols in methanol solutions of propyl 4-hydroxybenzoate (propylparaben) at T = (293.15 to 308.15) K: an acoustic and volumetric approach. (1st November 2020) - Thakur, Ashima; Juglan, K.C.; Kumar, Harsh; Kaur, Kirandeep
ABSTRACT: In the present investigation, densities and sound velocity of ethylene glycol and propylene glycol in the methanol solutions of propyl 4-hydroxybenzoate have been measured at different temperature and p  = 0.1 MPa experimental pressure. Apparent molar volume ( V ϕ ) and apparent molar isentropic compression ( K ϕ, s ) have been determined from the experimentally computed density and sound velocity data. The information about limiting apparent molar volume ( V ϕ 0 ) and limiting apparent isentropic compression ( K ϕ, s 0 ) and their respective empirical parameters such as Sv and Sk have been evaluated for each ternary mixture at working temperatures. The values of V ϕ 0 were computed to enlighten the intermolecular (solute–solvent, solute–solute and solvent–solvent) interactions present in the solution mixture, and ( V ϕ 0 ) values increase with rise in the temperature for all ternary system of present work. The K ϕ, s 0 shows the negative value due to pre-eminence of solute intrinsic effect over solvent intrinsic compressibility.